2016
DOI: 10.1186/s13052-016-0308-x
|View full text |Cite
|
Sign up to set email alerts
|

Serological screening for Celiac Disease in 382 pre-schoolers with Autism Spectrum Disorder

Abstract: BackgroundRecent investigations suggest a possible common genetic background between Autism Spectrum Disorders (ASD) and Celiac Disease (CD). However, studies regarding this association are scarce and often limited by the small sample sizes and/or large heterogeneity among ASD groups in terms of demographic and clinical features. The present study aims to investigate the overall CD prevalence (biopsy proven-CD patients plus screening detected tTG and EMA positive cases) in a large population of pre-schoolers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…Of the 767 ASD participants, ten were found to have CD making the pooled prevalence of CD in ASD 1.3%. All of these individuals came from the same study, which is the only one that confirmed significant findings [31]. In addition to this, Juncia et al (2018) noted GI symptoms in 34% of a pediatric ASD sample.…”
Section: Asd and Adhdmentioning
confidence: 54%
See 3 more Smart Citations
“…Of the 767 ASD participants, ten were found to have CD making the pooled prevalence of CD in ASD 1.3%. All of these individuals came from the same study, which is the only one that confirmed significant findings [31]. In addition to this, Juncia et al (2018) noted GI symptoms in 34% of a pediatric ASD sample.…”
Section: Asd and Adhdmentioning
confidence: 54%
“…ASD literature consisted of nine articles in total and comprised of 39,207 participants [31][32][33][34][35][36][37][38][39]. Only one found statistically significant findings, therefore only one concluded the need for routine CD screening within the ASD population [31]. This included 38,440 participants with a diagnosis of CD.…”
Section: Asd and Adhdmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have been inconsistent. While some studies report increased CD prevalence among individuals with ASD (8), other studies find no such associations (9)(10)(11).…”
Section: Introductionmentioning
confidence: 94%